Contextual factors influencing parents' assessments of family‐centred care in the paediatric emergency department: A qualitative study - Jennifer L. Rosenthal; Susan L. Perez; Heather M. Young (Nursing Open, 2023)
Abstract Aim To identify the contextual factors influencing parents' assessments of the family‐centredness of care received during a paediatric emergency department visit. Design A qualitative cross‐sectional case study. Methods We interviewed parents who were at their child's bedside during an emergency department encounter. We independently coded the first 3 transcripts and met to discuss the coding structure and to refine existing codes, add new codes and develop tentative categories. We repeated this process for every 3–5 transcripts until thematic saturation was reached. Results We conducted 16 interviews and identified 2 themes: (1) Not all parents expected physicians to provide family‐centred care in the emergency department and (2) feeling overwhelmed and powerless influenced parents' perceptions of family‐centred care. Poor family‐centred care worsened parents' sense of powerlessness and reinforced parents' low expectations from physicians. Similarly, low expectations and powerlessness exacerbated poor family‐centred care. Interventions are needed to break this cycle and improve family‐centredness of care.